Trauma e revolução: uma análise das obras de Jacques-Louis David (1784 a 1799) - Corso, Sofia (2019)
This work aims to analyze the works of Jacques-Louis David, a reference painter of the Neoclassical style, from 1784 to 1799. It is intended, through an interdisciplinary reading - relating art, history and psychoanalysis - to understand the stylistic transformations observed in works as an expression of a mutation in the link between virtue and terror. The hypothesis is that violence is intrinsically related to these changes, as well as the trauma caused by it. From the instruments of psychoanalysis, concepts such as mourning, perlaboration and trauma, will be used to apprehend the conflict between David's pre-revolutionary works and the changes that occurred in the face of the trauma caused by Terror. Subsequently, with the overthrow of Robespierre in 1794, David's work again changes and the complexity of the symbolic elements that make up his paintings as well. David is a rare case of an artist who became directly involved with the Revolution, not only to represent it artistically, but to experience it. As a survivor of the revolutionary period, he will live long enough to reevaluate events. In 1799, with the exhibition of the work The Sabines, we can perceive a significant change in the painter's conception of the function of art and its positioning on the directions taken by the French Revolution.